Assessment of the Role of Uterine Artery Doppler in Prediction of Preeclampsia: A Cross-Sectional Study from Rural Maharashtra - Dr. Abed Gulab Nagure; Dr. Mahe Darakshan M. Saleem; Dr. Anant A. Takalkar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: In recent years, ultrasonography is commonly used in measurement of fetal biometry and diagnosis of congenital anomalies and IUGR. Problem which still exists is identification of those pregnancies which are at risk of increased maternal and fetal morbidity as in pregnancy induced hypertension. Various biochemical tests used in screening of high-risk population for pre- eclampsia have lower positive predictive values, high cost and less patient compliance. 2 Doppler is a non-invasive method for evaluation of feto placental circulation without any disturbance to human pregnancy. Objective: To assess the role of uterine artery doppler in prediction of preeclampsia. Methodology: This is a prospective study done over a period of 2 years in St. philomena hospital-Bangalore from October 2010 to October 2012. Women with singleton pregnancy from 20-36 weeks of gestation attending St. philomena hospital and diagnosed as pre-eclampsia were subjected to uterine and umbilical artery Doppler along with morphology and biometry scan. Results: Majority of the patients were from 25-29 years age group i.e. 43% followed by 29% from above 30 years, 25% from 20-24 years and 3% from below 20 years age group. The mean maternal age was 27.2 years. 75.8% of cases had abnormal uterine artery S/D ratio. 83.9% of cases with abnormal RI. Uterine artery notch (54.8%) to be more than those without notch (45.16%). Conclusion: 83.9% of cases with abnormal RI. Number of cases with uterine artery notch (54.8%) to be more those without notch (45.16%). Cases with bilateral notch (55.88%) were more than those with unilateral notch (44.12%).